Noir fiction or the ineffectiveness of a category - Sánchez Zapatero, Javier (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The recent proliferation of texts ascribed to the genre "noir fiction" calls into question the relevance of this category, given the progressive dissolution of its most recognizable thematic, formal and pragmatic brands. The Spanish case presents very diverse variants that reveal the ineffectiveness of the concept.